(untitled) (Papeles, 2023)
Introduction: The purpose of this review paper is to report on the most representative models of argumentation used in the field of science education, as well as a description of their scope and contributions in the last two decades. Methodology: The research is based on a qualitative exploratory study with selection and categorization of research studies aimed at secondary science education and higher education teachers’ training using five databases to search for information. Following the approaches defined by the PRISMA methodology as well as inclusion and exclusion criteria, a systematic review of the selected documents is carried out. Results and Discussion: Supported on these criteria, the discussion drives coherently to the predominant argumentation models in science education and their scope for teaching proposals in future research studies. Conclusions: The paper points at some trends towards the exploration of argumentation models other than Toulmin’s, which continues being predominant nowadays, closer to language contemporary text and discourse analysis models.